National wrestling and horse racing in the cultural heritage of the Gagauz: from past to present - Elizaveta N. Kvilinkova (Историческая этнология)
The article examines the significance of wrestling and horse racing in the folk culture of the Gagauz people. It has been observed that sports competitions occupied an important place in the Gagauz calendar rituals, which indicates the ancient roots of these traditions among the Gagauz people. The Hederlez holiday in Gagauzia is explored through the prism of transformations and ethnocultural parallels. The basis of the traditional ritual of this holiday is revealed. The role of the national holiday Hederlez in the preservation and reproduction of Gagauz ethnocultural identity is analyzed. The author points out that in the 90s of the 20th century, during the struggle for their statehood, the Gagauz national elite placed emphasis on the Hederlez holiday, which became an important component in the process of ethnocultural development of the people and ethnic mobilization. The paper shows the role of freestyle wrestling tournaments and championships held in Gagauzia in the area of promoting the national sport. It is concluded that sports competitions, as an important component of the Gagauz people’s festive culture and the system of ethnic education, are a part of the historical and ethnogenetic memory of the Gagauz. In the process of historical development, these individual sports contributed to the formation of a number of traits among the Gagauz people that form the basis of the Gagauz national character: competitiveness, perseverance, desire to win, persistence in achieving goals, etc.